Antibacterial potential of celery (Apium graveolens L.) extract gel against Staphylococcus aureus - Martinus Ezra Sunarno; Anita Lidesna Shinta Amat; Arley Sadra Telussa; Prisca Deviani Pakan (Acta Biochimica Indonesiana, 2024)
Background: Staphylococcus aureus can cause furuncles or boils, painful nodules on the skin. Conventional topical therapies often lead to side effects such as contact dermatitis and pruritus, compounded by the increasing problem of antibiotic resistance. Natural ingredients like celery (Apium graveolens L.) offer promising alternatives due to their antibacterial properties and gentler effects. Objective: This study aimed to formulate a celery extract gel with ideal physical characteristics and evaluate its antibacterial potency against Staphylococcus aureus. Methods: Celery extract gel was prepared using HPMC, celery extract, methylparaben, propylparaben, and propylene glycol. Formulations with various celery extract concentrations were tested alongside mupirocin ointment (positive control) and gel base (negative control) against Staphylococcus aureus using the well-diffusion method. The results were analyzed using the One-Way ANOVA statistical test. Results: Celery extract gel demonstrated strong antibacterial potency at 25% (F1), 50% (F2), and 75% (F3) concentrations and very strong potency at 100% (F4). The One-Way ANOVA analysis showed a significant difference in the mean inhibitory zone diameter between treatment groups (p < 0.05). Conclusion: Celery extract gel exhibits significant antibacterial activity against Staphylococcus aureus, suggesting its potential as a natural alternative for topical therapy in managing skin infections.